Appreciating Everydayness through the Sabbath: An Open Pathway - Suereth, Russell (International Journal of Culture and History, 2023)
This article addresses our disconnect from the Sabbath and the everyday aspects of our daily lives. In our modern world, we neglect the Sabbath and the everyday. Through our industrial and technological cultures, our striving toward progress and material wealth hides the meaning we seek in our daily lives. The article describes the everyday in the context of the Sabbath. However, the article is not limited to a particular religion or any religion. The article's purpose is to open the ideas of the Sabbath to everyone so that more people may value the everyday aspects of their lives. This research suggests that greater awareness and participation in the Sabbath can lead to an appreciation of our everyday lives and enable meaningful experiences. The research considers literature in the context of everydayness. Accordingly, it employs literature that references our daily lives, or that could be twined into the structure of the everyday. The article describes the everydayness of our daily lives and how everydayness enables us to flourish. It shows how we neglect the Sabbath and everydayness in our hectic world. The article also discusses how the respite and rhythm of the Sabbath benefit us. Lastly, a reading depicts the close association of the Sabbath and our everyday lives. The reading is an example of participating in the Sabbath and suggests that such an engagement can lead toward greater awareness of the everyday.